Is your system fit for purpose? Female athlete health considerations for rugby injury and illness surveillance systems - Moore, I. S.; McCarthy-Ryan, M.; Palmer, D.; Perkins, J.; Verhagen, E. (European Journal of Sport Science, 2024)
This review discusses female-specific health considerations in injury and illness surveillance and provides rugby-specific recommendations for future surveillance. Identifying priority injury and illness problems by determining those problems with the highest rates within women's rugby may highlight different priorities than sex comparisons between men's and women's rugby. Whilst sports exposure is the primary risk for health problems in sports injury and illness surveillance, female athletes have health domains that should also be considered. Alongside female athlete health domains, studies investigating rugby injuries and illnesses highlight the need to broaden the health problem definition typically used in rugby injury and illness surveillance. Using a non-time-loss health problem definition, recording female-specific population characteristics, embedding female athlete health domains and having up-to-date injury and illness coding systems should be prioritized within surveillance systems to begin to shed light on potential interactions between sports exposure, health domains and, injuries and illnesses. We call for a collaborative approach across women's rugby to facilitate large injury and illness datasets to be generated and enable granular level categorization and analysis, which may be necessary for certain female athlete health domains. Applying these recommendations will ensure injury and illness surveillance systems improve risk identification and better inform injury and illness prevention strategies in women's rugby.